Situation Awareness in sports: A scoping review. (March 2022) - Huffman, Samantha; Crundall, David; Smith, Harriet; Mackenzie, Andrew
Abstract: Situation Awareness (SA) has been studied in many dynamic environments such as aviation. transportation, and medicine, but has not been extensively applied to sporting environments. Research from other areas suggests that SA is an important aspect of successful performance. The objectives of this scoping review were to identify what types of SA frameworks are used in sports, what methods are used to directly assess SA in sports, and what are the cognitive skills that have been linked to SA in sports. Seven databases were searched for peer-reviewed papers examining SA in a sporting context. The literature search revealed a scarcity of studies that directly describe SA within a sporting context. The most common frameworks described in the sporting literature were the three-level framework and Distributed Situation Awareness. The direct methods of measuring SA in sports varied and included the Situation Awareness Global Assessment Technique (SAGAT), Cognition Self-Assessment Tool (CSAT), and Random Number Cognition Test (RANCT) tools. Lastly, the cognitive skills linked to SA in sports included visual behaviours, anticipation, and decision-making. After evaluating the research, we argue there is potential benefit in applying SA to a sporting context but there are, currently, issues of validity and reliability in how SA is described and assessed in sports. Suggestions are made for how we might advance in this field of research. Highlights: There is a scarcity of studies pertaining to Situation Awareness in sports. There are different frameworks, assessment methods, and cognitive skills identified in sports Situation Awareness studies. The current literature highlights issues with validity and reliability in measuring Situation Awareness in sports. We propose a method which uses Synchronized Situation Awareness to measure group Situation Awareness across sports teams.